2022
DOI: 10.1097/dss.0000000000003387
|View full text |Cite
|
Sign up to set email alerts
|

Are Specific Body Sites Prone for Wound Infection After Skin Surgery? A Systematic Review and Meta-Analysis

Abstract: INTRODUCTION Identifying risk factors for wound infection may guide clinical practice for optimal use of perioperative antibiotic prophylaxis in dermatologic surgery. OBJECTIVE To summarize the current evidence whether specific body sites have higher risks for surgical site infections (SSI). Methods The systematic literature search included MEDLINE, Embase, CENTRAL, and trial registers. Only observational st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 30 publications
0
20
0
5
Order By: Relevance
“…The overall SSI risk further depends on underlying comorbidities and the operated body site. 10,31 The results of this study help to draw a risk profile for individual patients. This may support clinical guidance for a more restrictive use of PAP in dermatologic surgery.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The overall SSI risk further depends on underlying comorbidities and the operated body site. 10,31 The results of this study help to draw a risk profile for individual patients. This may support clinical guidance for a more restrictive use of PAP in dermatologic surgery.…”
Section: Discussionmentioning
confidence: 93%
“…The authors reported their results on the latter category previously. 10 In this article, the authors provide data on procedure-related risk factors for SSI.…”
mentioning
confidence: 99%
“…Overall, the cumulative infection rate of the two studies was very low, at about 3% (n = 551 procedures) 17 . Skin surgery on the trunk showed a significantly lower infection risk compared with other body regions at 2.5% (n = 80/3152 procedures) (RR 0.75; 95% CI 0.58–0.96) 16 . Based on a sufficient level of evidence, dermatologic surgery on the nose shows a low infection rate (1.8%; n = 40/2229 procedures).…”
Section: Procedure‐related Risk Factors For the Development Of Surgic...mentioning
confidence: 89%
“…Eine aktuelle systematische Übersichtsarbeit mit Metaanalyse hat dagegen die bisher verfügbare Evidenz zusammengefasst, und zwar unabhängig von der Komplexität der Verschlusstechnik oder davon, ob der Eingriff ein-oder mehrzeitig an einer bestimmten Körperregion erfolgt ist. 16 Hierbei bestätigte sich, dass dermatochirurgische Operationen an der Lippe (RR 1,90; 95% [Konfidenzintervall] KI 1,13-3,19) und den unteren Extremitäten (RR 2,42; 95% KI 1,43-4,07) statistisch mit einem signifikant höheren Infektionsrisiko einhergehen. Einschränkend muss bemerkt werden, dass nicht unterschieden wurde, ob Exzisionen am intakten Unterschenkel oder in Anwesenheit von Ulzera oder infizierten Fußwunden erfolgten.…”
Section: Eingriffsbezogene Risikofaktoren Für Die Entwicklung Postope...unclassified